2015
DOI: 10.1016/j.conb.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Human intracranial high-frequency activity during memory processing: neural oscillations or stochastic volatility?

Abstract: Intracranial high-frequency activity (HFA), which refers to fast fluctuations in electrophysiological recordings, increases during memory processing. Two views have emerged to explain this effect: (1) HFA reflects a synchronous signal, related to underlying gamma oscillations, that plays a mechanistic role in human memory and (2) HFA reflects an asynchronous signal that is a nonspecific marker of brain activation. Here, we review recent data supporting each of these views and conclude that HFA during memory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
119
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(126 citation statements)
references
References 47 publications
7
119
0
Order By: Relevance
“…Concretely, frequency bands below 30 Hz showed less power for CRs than Hits, with SPL channels showing the largest effect. This nontonal observation for low-frequency bands in ECoG data is commonly observed in the literature (52). Future research is needed to understand why the putative delta, theta, alpha, and beta bands, measured from left dorsal PPC, are not selectively involved in memory-guided decision making.…”
Section: Discussionmentioning
confidence: 68%
“…Concretely, frequency bands below 30 Hz showed less power for CRs than Hits, with SPL channels showing the largest effect. This nontonal observation for low-frequency bands in ECoG data is commonly observed in the literature (52). Future research is needed to understand why the putative delta, theta, alpha, and beta bands, measured from left dorsal PPC, are not selectively involved in memory-guided decision making.…”
Section: Discussionmentioning
confidence: 68%
“…Theta-gamma PAC was first described as a correlate of exploratory behavior in rodents (Buzsaki, 2002; Colgin, 2013) and has since been extensively studied in humans using ECoG, e.g., (Kahana et al, 1999). 3 It currently is widely accepted that high-frequency activity, e.g., gamma oscillations and spike discharge, reflect local processing (Buzsaki and Wang, 2012; Nir et al, 2007) whereas phase-synchronous slower activity, i.e., in the theta, alpha, beta frequency ranges (nominally, 4–30 Hz), coordinates excitability over widely separated parts of the brain (Bahramisharif et al, 2013; Burke et al, 2015; Ekstrom and Watrous, 2014; Jensen et al, 2014; van der Meij et al, 2012). This coordinating mechanism selectively links appropriate sensory, motor, task control, and memory modules according to instantaneous behavioral requirements (Fries, 2005; Helfrich and Knight, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that engagement of the extrinsic system predominantly suppresses alpha oscillations (Klimesch, 1999; Miller et al, 2007; Sederberg et al, 2003). Engagement of the intrinsic system has been variably reported as enhancing (Colgin, 2013) or suppressing (Burke et al, 2015; Crespo-García et al, 2016; Greenberg et al, 2015) theta oscillations. However, if these modulations (of either sign) are spontaneously coordinated across regions (i.e., in the task-free state), we may expect to observe spectrally specific spatial correspondences between BLP correlations and BOLD fMRI RSNs.…”
Section: Introductionmentioning
confidence: 99%
“…HFA can be thought of as an activation signal that measures the overall firing rate of many thousands of neurons at the mesoscopic level (30,31,49) and intracranial HFA recorded from a macroelectrode can be interpreted very similarly as multiunit activity recorded by a microelectrode, albeit on a different spatial scale. In a recent study of recognition memory, Wixted et al (29) demonstrated that hippocampal single-unit and multiunit recordings contain information pertaining to stimulus evidence (true target-lure status, irrespective of response choice).…”
Section: Discussionmentioning
confidence: 99%
“…Given that HFA is a spatiotemporally precise marker of neural ensemble activity (30,31), if hippocampal activity correlated with successful recognition performance at retrieval, then, depending on which theory is correct, it should correlate either with behavioral estimates of recollection only or with behavioral estimates of both recollection and familiarity. Seen through the lens of dual-process theories of recognition (12), hippocampal HFA should identify whether this structure uniquely supports recollection.…”
mentioning
confidence: 99%